Development of a Scoring Framework and Rapid Tool for Novice Screeners to Estimate the Seismic Risk of Damage in Low-Rise Concrete Buildings in the Philippines - Baniqued, Julius Rey; Pacheco, Benito (Philippine Engineering Journal, 2025)
Abstract – Low-rise concrete buildings in the Philippines have been frequently damaged in past earthquakes, underscoring the need for effective seismic risk assessment. As a preliminary step toward distinguishing buildings with high seismic risk, simplified screening tools that do not require users to be specialists or expert structural engineers are commonly used, reserving the time and expense associated with full structural engineering assessments. This paper proposes an improved scoring framework and a corresponding rapid tool for screening called SCREEN, based on the probable loss that estimates the seismic risk of damage in low-rise concrete buildings in the Philippines using parameters that can be conveniently gathered by screeners who are novices, i.e., not structural engineers but have backgrounds in building design or construction. The simplified SCREEN scores were derived to approximate the results of analysis of computational models of 128 buildings with variations in seven parameters including potential ground shaking intensity, type of occupancy, shape of structure, vintage of structure, builder of structure, main material whether CHB or reinforced concrete, and width of walls between supports. For validation, SCREEN was compared with two locally developed seismic screening tools using a sample set of six (6) concrete hollow block buildings and eleven (11) reinforced concrete buildings, demonstrating high sensitivity in identifying buildings needing engineering assessment. Meanwhile, its specificity in excluding low-risk buildings has not yet been as good. To minimize the risk of overlooking buildings with high seismic risk, this study prioritizes high sensitivity. It is recommended to test SCREEN further on a larger, diverse set of low-rise concrete buildings with independently assessed seismic risk. Keywords: concrete hollow block, reinforced concrete, sensitivity, specificity